Damage and interfacial debonding in composites - Voyiadjis, George Z.; Allen, David H., 1950- (Studies in applied mechanics;)
Written by leading authorities in the field of damage and micromechanics of composites, this book deals mainly with the damage impaired in composites due to different types of loading. It examines the different types of damage in composites in the fiber, matrix, debonding and delamination. It also reviews the theoretical characterization of damage, its experimental determination as well as the numerical simulation of damage.